1994
DOI: 10.1002/anie.199402201
|View full text |Cite
|
Sign up to set email alerts
|

Chiroporphyrins: An Approach to Asymmetric Catalysts with Stereocenters Near the Plane of the Porphyrin Ring

Abstract: COMMUNICATIONS ence experiments, which indicate the proximity of the marked CH, groups ( Fig. 1) to the pyridine protons, and by the small chemical shift of the pyridine protons which reflect the anisotropy of the pyridine ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…To study the steric and conformational ligand requirements to obtain stereocontrol of the reaction, several years ago we synthesised the cobalt(II) complex [84] 19 (Figure 8) of the chiroporphyrin already reported by Marchon et al [85] The cyclopropanation of α-methylstyrene by EDA catalysed by 19 afforded the corresponding cyclopropanes with low diastereo-and enantioselectivity. The observed experimental results were justified by theoretical calculations, which disclosed the existence of 19 as a pool of interconverting atropisomers.…”
Section: Cobalt-catalysed Reactionsmentioning
confidence: 99%
“…To study the steric and conformational ligand requirements to obtain stereocontrol of the reaction, several years ago we synthesised the cobalt(II) complex [84] 19 (Figure 8) of the chiroporphyrin already reported by Marchon et al [85] The cyclopropanation of α-methylstyrene by EDA catalysed by 19 afforded the corresponding cyclopropanes with low diastereo-and enantioselectivity. The observed experimental results were justified by theoretical calculations, which disclosed the existence of 19 as a pool of interconverting atropisomers.…”
Section: Cobalt-catalysed Reactionsmentioning
confidence: 99%
“…[2Ϫ4] Accordingly, different families of chiral catalysts such as vaulted binaphthyl, [5] basket-handle, [6] glycoconjugated, [7] threitolstrapped, [8] twin-coronet, [9] binaphthyl-capped, [10] seat, [11] and chiroporphyrins [12] have been prepared. Nevertheless, most of these studies reported individual examples of chiral catalysts, for which it was very often difficult to account for the observed enantioselectivity a priori.…”
Section: Introductionmentioning
confidence: 99%
“…The lower yields were obtained for alcohol esters of biocartol. Tetramethylchiroporphyrin 2a [8] (also called H 2 TMCP) and its metal complexes were needed in large amounts to screen their potential in enantiocontrol, [6,[9][10][11][12] so its yield was optimized to 20% using a 10 -3  concentration of reactants and a longer reaction time for porphyrinogen formation. Chiroporphyrin 2l was obtained in a surprisingly excellent yield (60%), which has been accounted for by the presence of complementary intramolecular hydrogen-bonding interactions between N-acylurea substituents which direct the cyclisation of the tetrapyrrolic intermediate.…”
Section: Syntheses Of Chiroporphyrins 2a-lmentioning
confidence: 99%
“…[7] Our investigations have revealed that biocartol methyl ester can be condensed with pyrrole to afford a prototypic chiral porphyrin which is obtained exclusively as the α,β,α,β atropisomer, and that we have called tetramethylchiroporphyrin. [8] We describe here the preparation and characterization of a series of D 2 -symmetric analogs, or chiroporphyrins, derived from various other esters and amides of biocartol, and from an urea derivative. Metal complexes of these chiroporphyrins have been shown to be useful as catalysts in enantioselective epoxidation and aziridination, [6,9] as hosts in chiral recognition of alcohols and β-amino alcohols, [10,11] and as chiral NMR shift reagent for amines.…”
Section: Introductionmentioning
confidence: 99%